Competencies for Climate Risk Management: making climate-smart agriculture operational - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
We developed the conceptual competency model for CRM, describing the capacities that farmers and extension workers require for the decision-making process in production systems based on climate information use. We will pilot it in 2021 in the WPF's PRO-RESILIENT initiative in Guatemala and the CRS's vanilla project in Uganda.